(untitled) (REMUNOM, 2025)
Autism is characterized by a markedly atypical development, commonly associated with difficulties in social interaction, repetitive behaviors, food selectivity, and restriction of activities and interests. The present study aims to evaluate the implementation of a balanced diet to reduce gastrointestinal disorders in children with Autism Spectrum Disorder (ASD). This is an integrative review research, based on quantitative data. The work was developed based on articles that explore the relationship between nutrition and autism, found on the Scientific Electronic Library Online (SciELO) platform. Data from the Center for Disease Control and Prevention (CDC) indicate an increase in autism awareness and diagnoses. In 2004, the CDC reported that 1 in 166 8-year-old children in the United States was diagnosed with autism. Already in 2021, this number rose to 1 in 36 children, according to a new CDC study. The discussion of the study highlights the importance of an adequate diet, rich in fundamental micronutrients for children with ASD, such as calcium, iron, zinc, folic acid, selenium, and vitamins A, D and B complex. These nutrients can attenuate characteristic symptoms of autism, contributing to an improvement in the quality of life of both patients and their families. It is concluded that, through a diet rich in specific micronutrients, it is possible to improve the quality of life of children with ASD, since these nutrients contribute to the reduction of symptoms associated with the disorder.